(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Banks are the most significant players in the Indianfinancial market because they are the biggest purveyors of credit and attractmost of the savings from the population. Banking plays very important role inthe economic development of all the nations of the world because a developedbanking system holds the key as well as serves as a barometer of economichealth of a country. The banking sector is core competency of the world economywhich influences the strength of every nation’s economy in the world economy.The overall development and growth of any economy depends more on the soundservices sector. The role of service sector in Indian economic development hasincreased by several notches from the fact that service sector which wascontributing only 20 percent during the independence time, now it iscontributing over 50 pc of GDP India. Indian economy is the fastest growingmajor economy in the world with GDP growth rate of 8.4 percent at the end ofthird quarter of 2007-08.